2019
DOI: 10.5194/acp-19-3857-2019
|View full text |Cite
|
Sign up to set email alerts
|

Links of climate variability in Arctic sea ice, Eurasian teleconnection pattern and summer surface ozone pollution in North China

Abstract: Abstract. Summer surface O3 pollution has rapidly intensified in China in the recent decade, damaging human and ecosystem health. In 2017, the summer mean maximum daily average 8 h concentration of ozone was greater than 150 µg m−3 in North China. Based on the close relationships between the O3 concentration and the meteorological conditions, a daily surface O3 weather index was constructed, which extends the study period to the historical period before 2007 and the projected future. Here, we show that in addi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…We used this method for daily and monthly analyses and selected the typical distribution of pollution to reverse the distribution of atmospheric circulation 26 . To link the spatial distribution of pollution in China to the APV, we used a teleconnection method 18 . This method is used to study the atmosphere on the planetary scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used this method for daily and monthly analyses and selected the typical distribution of pollution to reverse the distribution of atmospheric circulation 26 . To link the spatial distribution of pollution in China to the APV, we used a teleconnection method 18 . This method is used to study the atmosphere on the planetary scale.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, anomalous Arctic sea ice will also affect PM 2.5 pollution distributions in China on a climatic scale 17 . Thus, the APV reflects the impact of global climate change on air quality 18 . The PV is a large low-pressure system that is entrenched in the Arctic.…”
mentioning
confidence: 99%
“…Stratospheric ozone forms a protective layer that shields us from the Sun's harmful ultraviolet radiation. However, surface ozone is an air pollutant and has harmful effects on people and the environment, such as damaging human lungs (Day et al, 2017) and destroying agricultural crops and forest vegetation (Yue et al, 2017). Worldwide, polluted ozone events are more frequent and stronger in China than those that have taken place in Japan, South Korea, Europe and the United States (Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Employing the GEOS-Chem chemical transport model, Li et al (2018) found that rapid decreases in fine particulate matter levels significantly stimulated ozone production in NC by slowing down the aerosol sink of hydro-peroxy radicals. In addition, the meteorological conditions also influenced the ozone levels via modulation of the photochemical episodes and removal effects (Yin et al, 2019;Lu et al, 2019). Intense solar radiation accelerated chemical O 3 production (Tong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation